The immunopathogenesis of rheumatic immune adverse events from checkpoint inhibitors: prospects for targeted therapy. Issue 2 (March 2020) - Calabrese, Leonard H.; Calabrese, Cassandra
Abstract : Purpose of review: The introduction of checkpoint inhibitors as well as other allied advances in cancer immunology has made immunotherapy a pillar in the treatment of cancer. At the same time, these therapies have been associated with a remarkable array of immune-mediated toxicities observed in virtually every organ system, a portion of which are rheumatic in nature or multisystem in expression making them of particular relevance for rheumatologists. Recent findings: Most of our knowledge of these immune-related adverse events (irAEs) stems from clinical descriptive reports; we lack detailed understanding on immunopathogenesis for most complications. Therapeutic approaches are currently empiric and rely heavily on glucocorticoids and inhibitors of tumor necrosis factor. Serious consideration must now be given to advance our understanding of the immunopathogenesis of this emergent field and to exploit the full depth and breadth of the rich armamentarium of targeted therapies currently available to treat autoimmune and autoinflammatory diseases. Summary: irAEs are and will continue to increase in incidence and pose major hurdles to the continuing success and evolution of cancer immunotherapy. Basic and translational research into pathogenesis of irAEs and clinical trials of targeted therapies for these complications is urgently needed. Rheumatologists are well poised to actively contribute to the care and research of these complications.